Essential Oil Composition of Rose Flowers from Karangpring Village Jember District Extracted by Distillation and Enfleurage - Oktavianawati, Ika; Letisya, Nanda; Citra, Priscillia; Utari, Dwi Purwita; Winata, I Nyoman Adi; Handayani, Wuryanti; Nugraha, Ari Satya (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2019)
Karangpring is one tourist destination villages in Jember district which is popular with beautiful large rose field areas. Therefore, this area grows to be a leading producer of rose flowers in Jember district. However, the bulky presence of these flowers made its price becomes lower in regular days. Local community only uses and sells these fresh flowers as the flower for funeral. The rose flower has a great potency to be explored as a source of rose essential oil production. To date, there is no previous research on studying rose flowers from Karangpring village for its potency on the essential oil production. In this research, rose flowers were subjected to be extracted of its essential oil using two extraction methods, distillation, and enfleurage. Hydrodistillation resulted two phases of distillates, above part formed a cloudy white phase as a normal essential oil extracted from plants, and the lower phase was an aqueous phase containing rose hydrosols. Both phases of these condensates were analyzed using GCMS. Data explained that above phase, with a yield oil of 0.07%, only contains long-chain hydrocarbons such as n-nonadecane, n-heptadecane, 9-nonadecene, and eicosane, while the lower phase only contains 2-phenylethyl alcohol. On the other hand, enfleurage of fresh rose flowers resulted in 0.06% oil yield. GCMS analysis of this oil shows that 2-phenylethyl alcohol, eugenol, and phenylacetic acid are three major compounds which take more than 85% of total rose absolute. The results show that enfleurage is a better method for extracting rose oil in better quality than using the distillation method, in term of the variety of volatile components. Meanwhile, hydrodistillation is still benefiting from producing rose water that is qualified as an industrial additive agent for food and cosmetic productions or even a new potent of agromedicine products. Keywords: rose, rose oil, rose water, rose absolute, distillation, enfleurage.